2015
DOI: 10.5455/ajvs.202259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Progesterone in Treatment of Ovarian Inactivity in the Egyptian Dairy Parturient Buffalo-Cows

Abstract: I Inactive or nonfunctional ovaries are one of the most important reported causes of the prolonged postpartum anestrum that resulted to the delayed onset of estrus and inefficient breeding in buffaloes. The suggested study of progesterone in the blood serum of buffalo could be potentially useful as far as the hormone content that might reflect the postpartum condition in the buffalo-cows. This study aimed to evaluate the effect of exogenous progesterone in treatment of ovarian inactivity in the Egyptian dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Parmar (2013) suggested that estimation of the plasma P4 levels is helpful tool to detect the current reproductive/cyclical status of the animals and to diagnose early pregnancy with reasonable accuracy in freshly bred buffaloes. In our study, increasing P4 level in responded-conceived animals (heifers and cows) at all sampling times in comparing with responded-not conceived may be attributed to that high level of serum P4 during heat period improve conception rate in buffalo-cows (Bakr et al, 2015). Also, Parmar (2013) found that plasma P4 level was significantly (P<0.01) higher on day 21 post-AI in pregnant than in nonpregnant buffaloes (5.20±0.00 vs. 1.58±0.67 ng/ml).…”
Section: Plasma Progesterone Profilementioning
confidence: 49%
See 1 more Smart Citation
“…Parmar (2013) suggested that estimation of the plasma P4 levels is helpful tool to detect the current reproductive/cyclical status of the animals and to diagnose early pregnancy with reasonable accuracy in freshly bred buffaloes. In our study, increasing P4 level in responded-conceived animals (heifers and cows) at all sampling times in comparing with responded-not conceived may be attributed to that high level of serum P4 during heat period improve conception rate in buffalo-cows (Bakr et al, 2015). Also, Parmar (2013) found that plasma P4 level was significantly (P<0.01) higher on day 21 post-AI in pregnant than in nonpregnant buffaloes (5.20±0.00 vs. 1.58±0.67 ng/ml).…”
Section: Plasma Progesterone Profilementioning
confidence: 49%
“…Poor reproductive performance in dairy buffaloes in term of anestrus cases is a problem that reduces reproduction due to long days open and consequently long calving interval (Bakr et al, 2015) prolongation of the service period (Bailey et al, 1999) and increases economic losses to dairy industry. Anestrus in cattle and buffaloes is generally caused by ovarian dysfunction, silent ovulation and missing heat (Das and Khan, 2010;Sah and Nakao 2010) and generally observed in large number of buffaloes leading to their culling or slaughtering every year.…”
Section: Severalmentioning
confidence: 99%
“…The delay in the onset of cyclicity of the estrous cycle and initiation of ovulation during the postpartum period in buffaloes constitute a major problem and results in long postpartum anestrus and delayed breeding with consequent serious economic losses in milk production and efficient reproduction (Bakr et al, 2015). The present study was planned to study the occurrence of postpartum anestrus and compare the intensity of estrus in anestrus and estrus induced buffaloes of Jabalpur (M.P.…”
Section: Introductionmentioning
confidence: 99%